Stamps on bricks and tiles from Novae. Outline of chronolgy - Duch, Michał (Ośrodek Badań nad Antykiem Europy Południowo-Wschodniej. Uniwersytet Warszawski, 2017)
The First Italian legion produced building ceramics used in the construction of many buildings in the legion’s camp at Novae (Bulgaria), the remains of which have been investigated by archaeologists since 1960. The paper sums up current results of research on the chronology of artifacts of this kind, giving an overall review of the course and development of studies of stamped building ceramics in Novae to date.
Keywords: stamps, bricks, legio I Italica, Novae, Lower Moesia